THE PEOPLE'S GAME : HOW TO SAVE FOOTBALL - Neville, Gary; Draper, Rob (London : Hodder & Stoughton, 2023)
Football is the peoples game. A sport accessible to everyone and enjoyed by millions around the world. But football is broken. Beneath the glamorous sheen of the Premier League, it's a game that's rusting and rotten. The growing influence and wealth of the biggest teams is harming the game, leaving fans out of pocket and other clubs clinging to survival. Gary Neville has had a front-row seat in football for over 30 years, witnessing the sport at every level - as a player, a coach, a pundit and an owner. Most of all, he's a fan. The People's Game is Gary's vision for a brighter future. Drawing on interviews with those at the epicentre of the sports biggest issues - from the role of ownership to the lack of funding in the football league, the rise in racism and the future of the women's game - he explains how football has sleepwalked into this mess and offers a new way forward.
Originally published: 2022.
Includes bibliographical references
Keywords: Soccer -- Great Britain -- Management; Soccer -- Great Britain -- Finance; Soccer -- Great Britain -- Sociological aspects